Players with high physical fitness are at greater risk of injury in youth football - Leppänen, M.; Uotila, A.; Tokola, K.; Forsman-Lampinen, H.; Kujala, U. M.; Parkkari, J.; Kannus, P.; Pasanen, K.; Vasankari, T. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The aim of this study was to investigate physical fitness, football-specific skills, and their association with injury risk in youth football. Altogether 447 male and female players aged 9-14 years (median 12 years) participated in performance tests and prospective follow-up. The physical fitness tests included five-jump test for distance, 30-m sprint, football-specific figure of eight agility, countermovement jump, and Yo-Yo intermittent endurance test level 1. The football-specific skill tests included dribbling and passing tests. Injuries and exposure were registered during the 20-week follow-up. Our candidate risk factors were low/high level of physical fitness measured with a composite score of physical fitness tests and low/high level of football-specific skills measured with a composite score of dribbling and passing tests. Secondarily, we investigated performance in individual tests and their association with injury risk. During the follow-up, players reported 565 injuries (264 acute and 301 overuse injuries). High level of physical fitness was associated with increased rate of all injuries (age-, sex-, and mean team exposure—adjusted IRR: 1.28, 95% CI: 1.04-1.58). The level of football-specific skills had no influence on the overall injury rate. Burden of overuse injuries, but not acute injuries was significantly higher in most fit players compared with the players in the reference group (IRR: 2.09, 95% CI: 1.04-4.24). In conclusion, most fit players were at greater risk of sustaining injuries in youth competitive football.